Acculturation and risk of traffic crashes in young Asian-born Australian drivers. Issue 1 (28th September 2022) - Boufous, Soufiane; Möller, Holger; Patton, George; Woodward, Mark; Stevenson, Mark R; Senserrick, Teresa; Mclean, Rebecca; Cullen, Patricia; Wang, Amy; Rogers, Kris; Chen, Huei-Yang; Ivers, Rebecca Q
Abstract : The study examines changes over time in crash risk differences between young Australian drivers born in Asia and those born in Australia. Data from the 2003 baseline survey of the DRIVE cohort of 20 806 young drivers aged 17–24 years were linked to police, hospital and death data up until 2016. The association between country of birth and crash was investigated using flexible parametric survival models adjusted for confounders. Six months after baseline, the crash risk in Asian-born drivers was less than half that of their Australian-born counterparts (mean HR, MHR 0.41; 95% CI 0.29 to 0.57), only to increase steadily over time to resemble that of Australian-born drivers 13 years later (MHR 0.94; 95% CI 0.66 to 1.36). This is likely to be associated with acculturation and the adoption by young Asian-born Australian drivers of driving behaviour patterns akin to those born locally. This needs to be considered in future road safety campaigns.